Building A Synergy Between The Halal Industry And The Green Industry In The Maqasid Syari'ah Review As The Basis Of Islamic Economics - Achmad Fageh (Muhammadiyah University Press, 2022)
Industrial estates are usually reflected in the existence of a sure standardization. The halal industry gave birth to